University spin-offs and triple helix dynamics in regional innovation ecosystems: a comparison of technology intensive start-ups in Sweden. (6th March 2019) - Gabrielsson, Jonas; Politis, Diamanto; Billström, Anders
This study offers novel insights into how university spin-offs contribute to triple helix dynamics and the evolutionary processes of industrial renewal in regional innovation ecosystems. We analyse three groups of technology intensive start-ups: university spin-offs, corporate spin-offs, and independent technology start-ups. We compare and analyse various characteristics, functions, and processes among the three groups using primary data from a questionnaire survey conducted at 341 young firms operating in two technology intensive sectors in Sweden. Our findings suggest that university spin-offs differ from the other two groups with respect to their contribution to triple helix dynamics in regional innovation ecosystems. University spin-offs cooperate more closely with universities, conduct more in-house R&D, purchase more R&D services, and offer more innovative products/services in the introduction stage of their industry life cycles.